2015
DOI: 10.1007/s00213-015-4175-8
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine-induced brain activation in awake female nonhuman primates: a translational functional imaging model

Abstract: Rationale There is significant interest in the NMDA-receptor antagonist ketamine due to its efficacy in treating depressive disorders and its induction of psychotic-like symptoms that make it a useful tool for modeling psychosis. Objective The present study extends the successful development of an apparatus and methodology to conduct pharmacological MRI studies in awake rhesus monkeys in order to evaluate the CNS effects of ketamine. Methods Functional MRI scans were conducted in four awake adult female rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 49 publications
6
8
0
Order By: Relevance
“…They performed the phMRI scans during ketamine treatment and correlated the acute effects of ketamine with the alleviation of depression symptoms (BDI) 24hours post infusion. They found a similar pattern of acute ketamine-evoked BOLD activation in subjects with MDD to what has been shown previously in healthy control subjects (De Simoni et al, 2013; Deakin et al, 2008; Doyle et al, 2013) as well as in nonhuman primates (Maltbie et al, 2016). Further, they found that ketamine-induced BOLD activation in the rostral anterior cingulate cortex (rACC) correlated strongly (r=0.61) with alleviation of depression symptoms (measured by BDI).…”
Section: Pharmacological Imaging and The Behavioral Effects Of Ketaminesupporting
confidence: 80%
See 4 more Smart Citations
“…They performed the phMRI scans during ketamine treatment and correlated the acute effects of ketamine with the alleviation of depression symptoms (BDI) 24hours post infusion. They found a similar pattern of acute ketamine-evoked BOLD activation in subjects with MDD to what has been shown previously in healthy control subjects (De Simoni et al, 2013; Deakin et al, 2008; Doyle et al, 2013) as well as in nonhuman primates (Maltbie et al, 2016). Further, they found that ketamine-induced BOLD activation in the rostral anterior cingulate cortex (rACC) correlated strongly (r=0.61) with alleviation of depression symptoms (measured by BDI).…”
Section: Pharmacological Imaging and The Behavioral Effects Of Ketaminesupporting
confidence: 80%
“…Methods have also been developed that enable rhesus monkeys to undergo MRI scanning without the use of anesthesia and with minimal restraint stress (Murnane and Howell, 2010). A recent study has shown that awake rhesus monkeys display ketamine-induced BOLD activation (Maltbie et al, 2016) that corresponds closely in both magnitude and extent to what has been reported in humans (De Simoni et al, 2013; Deakin et al, 2008; Doyle et al, 2013). Moreover, pretreatment with risperidone attenuated the ketamine-induced changes in BOLD (Maltbie et al, 2016) to a similar extent as reported in humans (Doyle et al, 2013).…”
Section: Pharmacological Imaging and The Behavioral Effects Of Ketaminesupporting
confidence: 62%
See 3 more Smart Citations